Empowering Employees: The Role of Competence and Motivation in Productivity: Memberdayakan Karyawan: Peran Kompetensi dan Motivasi dalam Produktivitas - Dichiara, Cherryl Armetty; Farida (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2025)
The purpose of this study is to demonstrate how competence and career development affect workers’ productivity, with motivation acting as an intervening variable. The research was conducted at PT HK Realtindo, involving 115 employees. A quantitative methodology was employed, utilizing random sampling techniques. Data were analyzed using the Structural Equation Model (SEM) with Smart-PLS 3 software. The findings indicated that competence positively affects motivation, and career development also significantly influences productivity through its impact on motivation.